What's new in molecular genetic pathology 2022: immune checkpoint inhibitor biomarkers and select solid tumors - Patricia C. Tsang; Guoli Chen (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Predictive biomarker testing plays a critical role in targeted immuno-oncology, including the use of immune checkpoint inhibitors (ICI) for various solid tumors. Molecular advancements in cancers of the breast, kidney and brain have continued to propel tumor classification and precision therapy.